2005
DOI: 10.1021/cc049920u
|View full text |Cite
|
Sign up to set email alerts
|

Development of Combinatorial Chemistry Methods for Coatings:  High-Throughput Weathering Evaluation and Scale-Up of Combinatorial Leads

Abstract: Combinatorial screening of materials formulations followed by the scale-up of combinatorial leads has been applied for the development of high-performance coating materials for automotive applications. We replaced labor-intensive coating formulation, testing, and measurement with a "combinatorial factory" that includes robotic formulation of coatings, their deposition as 48 coatings on a 9x12-cm plastic substrate, accelerated performance testing, and automated spectroscopic and image analysis of resulting perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Specifically, materials such as catalysts,6 electronic and luminescent materials,7 ceramics, and polymers8, 9 have witnessed intense research efforts devoted toward identifying better formulations by optimizing a number of system variables. Bulk polymeric systems and thin polymer coatings, which are used in a number of industrially relevant applications, were rigorously subjected to HTE to comprehensively map out the structure–property relationship 4, 8–11. In this regard, recent efforts in combinatorial materials research carried out at the National Institute of Standards and Technology9, 12 and the Dutch Polymer Institute8, 10, 11 are noteworthy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, materials such as catalysts,6 electronic and luminescent materials,7 ceramics, and polymers8, 9 have witnessed intense research efforts devoted toward identifying better formulations by optimizing a number of system variables. Bulk polymeric systems and thin polymer coatings, which are used in a number of industrially relevant applications, were rigorously subjected to HTE to comprehensively map out the structure–property relationship 4, 8–11. In this regard, recent efforts in combinatorial materials research carried out at the National Institute of Standards and Technology9, 12 and the Dutch Polymer Institute8, 10, 11 are noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk polymeric systems and thin polymer coatings, which are used in a number of industrially relevant applications, were rigorously subjected to HTE to comprehensively map out the structure–property relationship 4, 8–11. In this regard, recent efforts in combinatorial materials research carried out at the National Institute of Standards and Technology9, 12 and the Dutch Polymer Institute8, 10, 11 are noteworthy. One major class of thin polymer films that has not yet been fully explored by the aforementioned studies pertains to systems involving surface‐anchored polymers 13.…”
Section: Introductionmentioning
confidence: 99%
“…[64] Several screening methods were developed to test the coatings for their key performance properties, which included adhesion to the substrate, [139] abrasion resistance, [140,141] and weathering. [142] Researchers at North Dakota State University have developed a comprehensive system for high-throughput coatings development with an initial focus on coatings for underwater marine applications. [69,132,133] Automated systems for polymer synthesis and characterization, coating formulation, [136] coating deposition, [68] and coating analysis have been implemented.…”
Section: Applications Of Combinatorial and High-throughput Experimentmentioning
confidence: 99%
“…These general concepts of advanced drug discovery are in principle applicable to materials discovery as well. Combinatorial methods, high-throughput experimentation, and computational modeling have been applied to a wide range of materials design challenges, including the discovery of semiconductors [24], coatings [25], catalysts [26], and light emitting phosphors [27]. Based on this, Gao et al concluded that advanced materials discovery tools will play an important role in the emerging nano-and biomaterials fields [28].…”
Section: Introductionmentioning
confidence: 99%